Edukasi virtual obat dexamethasone bukan penangkal COVID-19 - Hendera Hendera; Laila Eka Pratiwi; Memin Tri Ethik; Dina Ahsana (INDRA: Jurnal Pengabdian kepada Masyarakat, 2020)
The coronavirus 19 (COVID-19) outbreak is an infection caused by the acute respiratory syndrome coronavirus 2 (SARS-CoV-2) which are a pathogenic virus and highly contagious. The drug dexamethasone is only beneficial for patients infected with COVID-19 and has no effect on patients who are infected with mild symptoms nor can it prevent the entry of the COVID-19 virus. Taking dexamethasone without a doctor's prescription can trigger infection of the COVID-19 virus and have detrimental effects on the body. The purpose of this community service activity is to provide education that can increase understanding of dexamethasone which can not prevent us from getting infected by the COVID-19 and to inform the dangers of using dexamethasone that is not from a doctor's prescription. This is a quantitative research with a Pre-Experimental method using One Group Pretest-Posttest Design and the collecting data instruments used are multiple choice question types. The results of 30 participants complete data were analyzed using statistics with the Wilcoxon test with a P-value of 0,000 (P <0.05). The results showed that there was a significant effect on the use of educational methods in increasing participants' understanding of this drug. Furthermore, the N-Gain test was carried out with a result of 75.389%, so it concluded that the use of the educational method in the activity entitled "dexamethasone drug not an antidote to COVID-19" was considered quite effective in increasing the knowledge of participants who were facilitated by the pre-test and post-test.